Clinical Characteristics and Prognostic Risk Factors of Patients With Proven Invasive Pulmonary Aspergillosis: A Single-Institution Retrospective Study - Tong, Xiang; Liu, Tao; Jiang, Kexin; Wang, Dongguang; Liu, Sitong; Wang, Ye; Fan, Hong (Frontiers in Medicine, 2021)
Background: The mortality and burden of medical costs associated with invasive pulmonary aspergillosis (IPA) is very high. Currently, the clinical features and prognostic factors of patients with proven IPA are not very clear, especially in the Chinese population. In this retrospective analysis, we aimed to identify the clinical features and prognostic factors of patients with proven IPA. Methods: The diagnostic criteria for proven IPA were based on the international consensus of the EORTC/MSG. Data of patients with proven IPA at the West China Hospital of Sichuan University between January 2012 and December 2018 were collected. The optimal cut-off value of continuous variables was determined by Receiver Operating Characteristic curve and maximum Youden’s index. Finally, using the Cox regression analysis to identify correlations between the clinical parameters associated with morbidity. Results: A total of 117 patients with proven IPA were included in the study, and 32 (27.4%) patients died during the follow-up period. Compared with the survivor group, elderly, patients with comorbidities, and patients undergoing chemotherapy and the level of inflammatory biomarkers (erythrocyte sedimentation rate, platelet count, interleukin-6, C-reactive protein (CRP)) in the non-survivor group were higher, while the albumin level was lower (P=0.018). The imaging features were consolidation, nodules, cavities, pleural effusion, ground-glass shadows, and halo signs in order. Overall, 41.0% patients had mixed imaging features. The results suggested the most appropriate cut-off value of age and CRP were 60 years and 14.1mg/L respectively. The multivariate Cox regression analysis suggested that advanced age (>60 years) (hazard ratio [HR]: 10.7, confidence interval [CI]: 2.5–44.9, P<0.001), undergoing chemotherapy (HR: 9.5, CI: 2.7–32.9, P<0.001), presence of pleural effusion (HR: 5.74, CI: 1.6–20.8, P=0.008), and increased CRP levels (>14.1mg/L) (HR: 6.3, CI: 1.2–34.3, P=0.033) were risk factors for all-cause mortality in patients with proven aspergillosis. Conclusions: This study showed that the prognosis of proven IPA is poor, and the age >60 years, undergoing chemotherapy, pleural effusion on CT image, and CRP levels >14.1mg/L may be as risk factors for mortality in patients with proven IPA. large samples and real-world studies are needed to confirm these results in the future.